A single mutation in an enteric virus alters tropism and sensitivity to microbiota - Andrea K. Erickson; Danica M. Sutherland; Olivia L. Welsh; Robert W. Maples; Terence S. Dermody; Julie K. Pfeiffer (Proceedings of the National Academy of Sciences, 2025)
Many enteric viruses benefit from the microbiota. In mice, microbiota depletion reduces infection by noroviruses and picornaviruses. However, Reovirales viruses are outliers among enteric viruses. Rotavirus infection is inhibited by bacteria, and we determined that several reovirus strains have enhanced replication following microbiota depletion. Here, we focused on an isogenic pair of reoviruses that have opposing infection outcomes after microbiota depletion. Microbiota depletion reduces infection by reovirus strain T3SA+ but increases infection by strain T3SA−. These strains differ by a single amino acid polymorphism in the σ1 attachment protein, which confers sialic acid binding to T3SA+. Sialic acid binding facilitates T3SA+ infection of intestinal endothelial cells, while T3SA− inefficiently infects intestinal epithelial cells due to restriction by microbiota-driven, host-derived type III interferon responses. This study enhances an understanding of the interactions of enteric viruses, the microbiota, intestinal tropism, and antiviral responses.